Kissing the sky : a novel - Patton, Lisa (Lake Union Publishing, 2026)
"It's the summer of '69. While her peers revel in free love and rock and roll, Suzannah is home from college, sequestered inside her conservative Southern home. Her domineering father has condemned rock music and driven away her best friend. She's counting the days until fall. But everything changes when her free-spirited best friend, Livy, resurfaces, urging Suzannah, a talented singer, to join her for three days of peace and music in upstate New York. Fed up with her father's rules and fearful for her brother's fate in Vietnam, Suzannah agrees to the road trip, sneaking off without her parents' knowledge. Miles outside her comfort zone, the electrifying bedlam of Woodstock jolts her into a journey of self-transformation. But it's not all incense and peppermints. Suzannah's falling hard for Leon, a boy she meets at the festival, and the seductive bud of first love conceals a thorn of heartache. Lies uncover betrayal, and Livy's wild behavior leads to a startling revelation"--Amazon.com.